Monetary theory and policy - Walsh, Carl E. (MIT Press, 2017)
"This third edition reflects the latest advances in the field, incorporating new or expanded material on such topics as monetary search equilibria, sticky information, adaptive learning, state-contingent pricing models, and channel systems for implementing monetary policy. Much of the material on policy analysis has been reorganized to reflect the dominance of the new Keynesian approach. Monetary Theory and Policy continues to be the only comprehensive and up-to-date treatment of monetary economics, not only the leading text in the field but also the standard reference for academics and central bank researchers."--Provided by publisher.